Factors Affecting Repurchase Intention Of Paracetamol Users In Jabodetabek - Andri Kurniawan; Unggul Kustiawan (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to investigate the relationship between brand heritage, brand trust, brand loyalty, repurchase intention, and brand strength in several paracetamol brands of PT. Oryza Medica Indonesia in the Greater Jakarta area, Indonesia. Data collection was carried out online with the population, namely users of the paracetamol brand PT. Oryza Medica Indonesia, of as many as 138 people. This type of quantitative research method uses SEM-Lisrel analysis. The results of the study show that brand heritage has a positive influence on brand trust. In addition, brand heritage also has a positive influence on brand strength. Furthermore, brand trust has a positive influence on repurchase intentions. However, brand trust does not have a positive effect on brand loyalty. Furthermore, brand trust has a positive influence on repurchase intentions. In addition, it was found that brand strength has a positive influence on brand loyalty. In the context of paracetamol users, this study emphasizes the importance of increasing consumer trust and loyalty to increase repurchase intention by providing insight into the importance of understanding and managing relationships in the context of brand investment by providing products and services that meet customer expectations to strengthen brand positions and maintain market share. strong market. Keywords: Brand Heritage, Brand Trust, Brand Loyalty, Repurchase Intention, Brand Strength